2019
DOI: 10.3390/nano10010065
|View full text |Cite
|
Sign up to set email alerts
|

Facile Fabrication of Flexible Electrodes and Immobilization of Silver Nanoparticles on Nanoscale Silicate Platelets to Form Highly Conductive Nanohybrid Films for Wearable Electronic Devices

Abstract: This study investigated films with remarkably high electrical conductivity after they were easily prepared from organic/inorganic nanohybrid solutions containing an organic polymeric dispersant and two-dimensional nanoscale silicate platelets as the inorganic stabilizer dispersed with silver nanoparticles. Transmission electron microscopy shows that the production of silver nanoparticles synthesized by the in situ chemical reduction of AgNO3 in an aqueous solution by N,N-dimethylformamide results in an average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Following a previous study, the polymeric dispersant PIB–POE–PIB triblock copolymer was synthesized through amination and further imidization between PIB-SA and POE-2000 (molar ratio: 2:1), as shown in Figure S4 of the Supporting Information. PIB-SA (25.0 g, 2 mol) was dissolved in THF (200 mL) in a three-necked round-bottom flask; then, POE-2000 (19.0 g, 1 mol, dissolved in THF (152 mL) in advance) was added dropwise, and a mechanical stirrer and thermocouple were used for mixing and heating, respectively. The mixture was allowed to react at 25 °C for 3 h under constant stirring before being analyzed by Fourier transform infrared spectroscopy (FT-IR), as shown in Figure S5 of the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Following a previous study, the polymeric dispersant PIB–POE–PIB triblock copolymer was synthesized through amination and further imidization between PIB-SA and POE-2000 (molar ratio: 2:1), as shown in Figure S4 of the Supporting Information. PIB-SA (25.0 g, 2 mol) was dissolved in THF (200 mL) in a three-necked round-bottom flask; then, POE-2000 (19.0 g, 1 mol, dissolved in THF (152 mL) in advance) was added dropwise, and a mechanical stirrer and thermocouple were used for mixing and heating, respectively. The mixture was allowed to react at 25 °C for 3 h under constant stirring before being analyzed by Fourier transform infrared spectroscopy (FT-IR), as shown in Figure S5 of the Supporting Information.…”
Section: Methodsmentioning
confidence: 99%
“…Electrodes using the composition of nanosilver/dispersant/GO have demonstrated high conductivity. However, silver is expensive and the characteristics of air oxidation have not been addressed in detail [6,[41][42][43], while copper nanoparticles are hindered by safety concerns. Studies have shown that in 2013, Cohen et al [44] found that the toxicity of CuNPs firstly penetrate directly into cells from CuNPs, and secondly, Cu 2+ ions diffuse into the cytoplasm.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the interaction between the functional groups on the surface of the nanomaterial and PVDF (or its copolymers) can be harnessed to promote the β-phase [ 23 ], thereby improving the crystallinity and piezoelectric properties of PVDF (or its copolymers). In our laboratory, we have comprehensively studied the dispersion and stabilization of inorganic nanomaterials by polymeric dispersants [ 24 , 25 , 26 , 27 ]; the molecular structure of the polymeric dispersant has been used to interact with the inorganic nanomaterial via π–π stacking and lone pair interactions, thereby enhancing the dispersion and stability of the inorganic nanoparticle in solution. To our knowledge, no research has discussed the seismocardiography influence of carbon nanomaterials of different dimensions on piezoelectric polymers.…”
Section: Introductionmentioning
confidence: 99%